Franz Sigel papers - Sigel, Franz, 1824-1902.
Pages from a letterpress book (1863 March 21-1865 June 2) containing Sigel's letter of commendation for Union army officer James M. Kennedy and other papers; and ALS (1870 January 9) from Sigel to W. A. Knapp, adjutant general of Ohio. Includes preservation photocopies.
German army officer. Immigrated to the U.S., 1852. Union army officer during the Civil War and editor of German language newspapers in Baltimore, Md., and New York, N.Y.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Kennedy, James M., -- army officer; Knapp, W. A. -- Correspondence; United States. -- Army -- Officers; Ohio -- Militia; United States -- History -- Civil War, 1861-1865.; Army officers; Publishers